Training of subject specialist librarians in developed countries: a model offering regarding medical librarianship for Turkey - Coşkun, Burak; Sert, Işıl İlknur (Journal of the European Association for Health Information and Libraries, 2021)
Medical librarianship (ML) has become one of the vital issues today. Expert librarians /information professionals can assist their users in cooperation with academics on issues that fall within their field. In developed countries, specialist librarianship gains importance in Information and Document Management (IDM) education. This study aims to present an idea about the training given in medical librarianship first and then in other specialties (Law Librarianship, Engineering Librarianship, etc.).